Strategi Pengembangan Daya Tarik Dago Tea House Sebagai Alternatif Wisata Budaya di Jawa Barat - Kartika, Titing; Ruskana, Rosman; Fauzi, Mohammad Iqbal (Universitas Pendidikan Indonesia, 2018)
Dago Tea House is a cultural tourism based or commonly called cultural tourism that offers a variety of unique arts and cultures. This Study aims to identified and analyzed the existing tourist attraction in Dago Tea House from the internal aspects (strengths and weaknesses) of external aspects (opportunities and threats) and then formulate the direction of optimize of tourist attraction in a proper planning and strategy for Dago Tea House in how to be an alternative of culture tourism in Bandung city. The research method used is qualitative descriptive which is assisted by using Analysis SWOT. From the research and analysis in terms of general conditions and the attraction, amenity, accessibility and ancillary of Dago Tea House and got a score 2.74 in IFAS Matrix and 2.57 in the EFAS matrix. The result of rating analysis and weighting of internal and external aspect shows that Dago Tea House is in Quadrant 1 supporting the aggressive strategy which can be concluded include optimizing of tourist attraction and promotion.